DFT insights into the structural, mechanical, electronic, optical, and thermal properties of Cr2AC (A = Si, Al, Ga, Ge, and P) MAX phases carbides - Md. Nurul Amin; Abdulla Al Faysal; Ahmed Azzouz-Rached; Faisal Islam Chowdhury; Jamal Uddin; Join Uddin; Jahidul Islam; Ali Reza Piyal; Anjan Kumar Chowdhury; A. K. M. Rezaur Rahman (AIP Advances)
This work examines the structural, electronic, mechanical, optical, and thermal properties of Cr2AC (A = Si, Al, Ga, Ge, and P) MAX phases using density functional theory. These properties are investigated through first-principles calculations within the generalized gradient approximation using the CASTEP software package. The Cr2AC phases exhibit metallic behavior, as confirmed by their electronic band structures, with no bandgap present. Regarding mechanical properties, Cr2SiC and Cr2GeC display superior ductility due to their covalent bonding, while Cr2AlC and Cr2GaC are more brittle due to ionic bonding. The elastic constants confirm the mechanical stability of these compounds, and the analysis of their anisotropic mechanical behavior indicates varying degrees of direction-dependent elasticity. For optical properties, reflectivity and refractive indices calculations suggest that these materials could be useful for optoelectronic applications. Thermal properties, including Grüneisen parameters (γ) and Debye temperatures (ΘD), indicate that Cr2AlC and Cr2PC exhibit exceptional thermal stability, making them promising candidates for thermal barrier coatings. These MAX phases are mechanically stable, and their tunable properties, driven by A-site substitution, expand the range of potential applications in areas such as high-temperature and optoelectronic devices used in hostile environments.